Analyze the Impact of Digital Technology on People's Social Life - stepani, gabriella; Hartika, Dewi; Regar, Nisa Andriani; Sugihwarni, Popy; Malasari, Tiur (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The development of digital technology brings a significant impact on people's social life, creating media integration in daily life. These advancements provide positive impacts such as increased access to information, ease of communication, economic growth, and improved quality of life. However, the negative impacts include problems in education and social aspects, including the risk of concentration disorders and pressure from social media. This research uses a qualitative descriptive method to understand this phenomenon.The results show that digital technology makes positive contributions such as increasing access to information and strengthening social communication. However, the negative impacts include over-dependence that disrupts daily activities, a decrease in direct social interactions, the risk of depression and anxiety, and the spread of fake news that can lead to conflict.